Swage casting of A380 alloy - Lus, Huseyin Murat; Turkeli, Altan; Kinikoglu, Nihat Gurbuz (ELSEVIER SCI LTD, 2011)
Swage casting is a new casting technique which combines the advantages of squeeze, centrifugal and semi-solid casting methods. In this new casting method, components with one rotating axis can be produced on a swage casting machine from molten metal in a one-step operation. A shape like a bomb-body is chosen to demonstrate the advantages of this new method by using A380 Al-Si-Cu alloy. The same alloy is also cast with centrifugal and squeeze casting methods. In this study, the swage casting method and its features are briefly described. The final microstructures, mechanical properties and amount of porosity of the cast pieces produced by squeeze, centrifugal and swage casting methods are compared. Swage cast pieces showed a different composition of microstructure that consists of fine dendritic particles at the chill ends and a mixture of spherical and rosette shaped particles at the core. The swage cast pieces also have a slightly higher mechanical strength as indicated by tensile strength and Brinell hardness values. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: METAL-ALLOYS; BEHAVIOR; Materials Science